1994
DOI: 10.1016/0921-4534(94)90808-7
|View full text |Cite
|
Sign up to set email alerts
|

HREM on Tc=14.5 K superconducting ThPd2B2−xC

Abstract: The compound ThPd2B2C has been studied with high-resolution electron microscopy and electron diffraction. ThPd2B2_xC adopts the LuNi2BEC structure with a layer sequence (BrNi2-B=-LuC)n in which the B composition and the exact position of the C are still uncertain. No intergrowths or planar defects are observed. The c-axis in the thinner parts of the crystals ( < 50 nm) was observed to decrease up to about 0.5 nm when irradiated by the electron beam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…(2) this phase is absent in the specimen 1331a which shows no superconducting transition at 14.5 K; (3) the structure as determined by HREM [ 8 ] indicates that this phase adopts the LuNi2BzC structure, a structure which has shown superconductivity for many analogous compounds. The plate-like morphology of ThPd2BEC is similar to the shapes of the crystals of LUNiEBEC [ 10 ] and YPdzBEC [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(2) this phase is absent in the specimen 1331a which shows no superconducting transition at 14.5 K; (3) the structure as determined by HREM [ 8 ] indicates that this phase adopts the LuNi2BzC structure, a structure which has shown superconductivity for many analogous compounds. The plate-like morphology of ThPd2BEC is similar to the shapes of the crystals of LUNiEBEC [ 10 ] and YPdzBEC [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the superconducting phase is YPd2B2C having a structure quite similar to that of LuNi2B2C. Sarrac et al [ 3 ] have reported the presence of two superconducting phases in the system Th-Pd-B-C, one with composition YPd2B2C having a Tc of 14.5 K and the LuNi2B2C structure [ 3,8 ] and one with a Tc of 21 K whose composition and structure are not known. The problem of identifying the 21 K phase in the system Th-Pd-B-C seems to be similar to the identification of the 23 K phase in the system Y-Pd-B-C, since in both cases it is difficult or impossible to synthesize single-phase material.…”
Section: Ssdio921-4534(94)oo546-xmentioning
confidence: 99%
See 3 more Smart Citations